Influence of feeding accuracy on the performance of Aberdeen Angus × Ayrshire and Charolais × Ayrshire crossbred suckler cows and their progeny - Manninen, Merja; Taponen, Juhani (Elsevier, 2004)
Thirty-two Aberdeen Angus-Ayrshire cows (AbAy), initial live weight (LW) 425 kg in Experiment 1 and 506 kg in Experiment 2, and 32 Charolais-Ayrshire cows (ChAy), initial LW 450 kg in Experiment 1 and 551 kg in Experiment 2, were selected for the two experiments. At the onset of Experiment 1, the animals were first-calf heifers pregnant to an Ab bull and in Experiment 2 second-calf cows pregnant to a Hereford bull. In both experiments, four treatments in a 2 × 2 factorial arranged design consisted of the two breeds and two feeding accuracies, (Accurate and Inaccurate; A and IA). In Experiment 1, the day-to-day variation in the roughage offered ranged up to ± 40%. In Experiment 2, the same variation was used in two weeks periods. Forage consisted of grass silage and hay, additionally straw in Experiment 2. Milled barley was offered to the cows pre and post partum. The objective was to study the effects of treatments on cow feed intake, live weight, body condition, milk production, dystocia, fertility and calf performance. In addition, the achieved feeding level for non-mature beef-dairy crosses was evaluated. In Experiment 1, the AbAy and ChAy cows received daily during the entire indoor period an average 73.1 and 81.6; in Experiment 2, 89.1 and 92.2 MJ ME, respectively. In both experiments, variation of roughages offered had only minor effects on cow performance. Reproduction was not affected by the feeding accuracy. Treatments had no effect on milk production, which averaged 10.8 and 12.6 kg/d in Experiments 1 and 2, respectively. The milk protein content of the ChAy cows was higher (p<0.01) than that of the AbAy cows (Exp.1: 32.7 vs. 31.0 g/kg, Exp.2: 31.9 vs. 29.3 g/kg). The dystocial cases observed were not related to the treatments. In Experiment 1, calves on diet IA tended to grow better pre-weaning than those on diet A (p=0.08, 1325 vs. 1296 g/d). In both experiments, live weight gain pre-weaning was better for males than for females (Exp.1: 1398 vs. 1224 g/d, p<0.05 and Exp.2:1453 vs. 1295 g/d, p<0.05). Accurate feeding is not necessary for young beef-dairy crosses if the total amount of feed, and thus energy offered over a period of a few weeks, is adequate to fulfill the energy requirements. The amount of energy offered for both types of non-mature crossbred cows proved to be sufficient on the basis of the performance data.
Keywords: Ko; ruokintatarkkuus; kuntoluokka; emolehmät; nautakarja; märehtijät; ruokinta; rehut; maidontuotanto; hedelmällisyys; suckler cows; cattle; feeding; milk production; beef; fertility; reproduction; feeding accuracy; body condition